Light Nonaqueous-Phase Liquid Hydrocarbon Weathering at some JP-4 Fuel Release Sites - D. H. Kampbell; C. B. Snyder; D. C. Downey; J. E. Hansen (Journal of Hazardous Substance Research, 2001)
A fuel weathering study was conducted for database entries to estimate natural light, nonaqueousphase liquid weathering and source-term reduction rates for use in natural attenuation models. A range of BTEX weathering rates from mobile LNAPL plumes at eight field sites with known release dates was documented. Freephase fuel BTEX weathering rates varied among sites and were influenced by many factors. First-order weathering rate for five JP-4 fuel sites was 16%/year. Benzene and toluene exhibited higher weathering rates than ethylbenzene and xylene, as expected, because of higher water solubility. The primary weathering mechanism of mobile LNAPL was dissolution. Meaningful determination of mobile LNAPL weathering rates for BTEX in the fuels was difficult because of the large ranges of initial BTEX values.
Keywords: weathering; JP-4; LNAPL